Um estudo de “um belo dia” na perspectiva da gramática de construções - Silva, Michele Denise da (2017)
This research is founded on the project “Rede de estudos da língua portuguesa ao redor do mundo”, headquartered at the Faculty of Letters of the Federal University of Goiás, and has as one of its objectives to provide subsidies for the promotion and teaching of Brazilian Portuguese from Results of analyzes of real uses of that language. In this context, we describe and analyze the pairing "um belo dia", from the theoretical perspective of LFCU, more specifically, the Construction Grammar. The central hypothesis is that the microconstruction "um belo dia" undergoes a process of change: from a more concrete use, active in the organization of the predication, until a more abstract use, functioning at the textual level, aiding in the macro-organization of the narrative. From this perspective it is understood that the language consists of cognitive, sociointeractional and cultural processes, and language is seen as a complex adaptive system with a fluid frame. Studies in the LFCU analyze and try to clarify the grammatical phenomena of the usage of the language and have as one of its theoretical contributions the theory of Constructions Grammar, which defines the grammatical constitution as a conceptual network, a system of cognitively interconnected entities (LANGACKER, 2008, TOMASELLO, 2010, TRAUGOTT, TROUDALE,2013) and language as a network of relationships that is organized in the use (TROUGOTT and TROUSDALE, 2013, CROFT, 2001, GOLDBERG, 2006). Suported on this theoretical conception, we present the results of the research that involves the uses of the microconstruction "um belo dia" ("a beautiful day") from a panchronic perspective. The corpora chosen for the research are o Corpus do grupo Discurso e Gramática (D&G), e o Corpus Fala Goiana. More specifically, the aim is to analyze the form and function of "a beautiful day", from the syntactic, morphological, phonological, semantic, pragmatic and speech-functional properties (CROFT, 2001) of this microconstruction, assuming that the uses detected in the corpora present different degrees of abstraction, indicating a construccionalizacion. The analyzes confirmed the hypothesis that the microconstruction "um belo dia" in its more abstracted use acts at the textual level, aiding in the macro-organization of the narrative, influencing the reception of the reader and its involvement in the discursive plot.